Effects of zero-sequence transformations and min-max injection on fault-tolerant symmetrical six-phase drives with single isolated neutral - Munim, Wan Noraishah Wan Abdul; Tousizadeh, Mahdi; Che, Hang Seng (Korean Institute of Power Electronics, 2019)
Recently, there has been increased interest in the study of multiphase machines due to their higher fault-tolerant capability when compared to their conventional three-phase counterparts. For six-phase machines, stator windings configured with a single isolated neutral (1N) provide significantly more post-fault torque/power than two isolated neutrals (2N). Hence, this configuration is preferred in applications where post-fault performance is critical. It is well known that min-max injection has been commonly used for three-phase and multiphase machines in healthy condition to maximize the modulation limit. However, there is a lack of discussion on min-max injection for post-fault condition. Furthermore, the effects in terms of the common-mode voltage (CMV) in modulating signals has not been discussed. This paper investigates the effect of min-max injection in post fault-tolerant control on the voltage and speed limit of a symmetrical six-phase induction machine with single isolated neutral. It is shown that the min-max injection can minimize the amplitude of reference voltage, which maximizes the modulation index and post-fault speed of the machine. This in turn results in a higher post-fault power. © 2019 KIPE.